Clonal Progression of Prostate Cancers from Gleason Grade 3 to Grade 4 - Sowalsky, Adam G. (2012)
Low-grade prostate cancers (Gleason pattern 3 [G3]) detected on needle biopsies are generally viewed as indolent and suitable for conservative management with only interval repeat biopsies to monitor by watchful wating. Higher grade tumors eventually emerge in 20–30% of these cases, but this process may only reflect incomplete sampling on the initial biopsy, such that it remains unknown how generally G3 tumors progress to higher grades. In this study, we examined a series of adjacent G3 and Gleason pattern 4 (G4) tumors in radical prostatectomy specimens and found that all were concordant for the TMPRSS2:ERG gene fusion. Using hybrid-capture and deep sequencing in four fusion-positive cases, we found that adjacent laser-capture microdissected G3 and G4 tumors had identical TMPRSS2:ERG fusion breakpoints, confirming their clonal origin. Two of these G3 tumors had deletion of a single PTEN gene that was also deleted in the adjacent G4, while the G4 tumors in two cases had additional PTEN losses. These findings establish that a subset of G3 tumors progress to G4, or emerge from a common precursor. Further, they show that G3 tumors which progress to G4 may have molecular features distinguishing them from G3 tumors that do not progress. Thus, determining the spectrum of these genetic or epigenetic features may allow for the identification of G3 tumors on needle biopsies that are truly indolent, versus those that have the potential to progress, or that may already be associated with a G4 tumor that was not sampled at the initial biopsy, therefore requiring more aggressive surveillance or intervention.